On the problem of Frattini duality in the theory of Fitting classes - Vorob’ev, N. T.; Nanying, Yang; Shuya, Zhao (Ukrains’kyi Matematychnyi Zhurnal, 2019)
UDC 512.542 We determine the application of the Frattini duality to the description of multiple local Fitting classes. In particular, we establish a necessary and sufficientcondition for the local Fitting class to be a formation.